Psychometric validation of three new condition-specific questionnaires to assess quality of life, symptoms and treatment satisfaction of patients with aortic aneurysm - Jacquelyn Romaine; George Peach; Matt Thompson; Robert J. Hinchliffe; Clare Bradley (SpringerOpen, 2019)
Abstract Background To evaluate the psychometric properties of three new condition-specific questionnaires designed to assess outcomes amongst patients under pre-operative surveillance for a small abdominal aortic aneurysm (AAA) or who have undergone aneurysm repair. These tools are the Aneurysm-Dependent Quality of Life measure (AneurysmDQoL), the Aneurysm Symptom Rating Questionnaire (AneurysmSRQ) and the Aneurysm Treatment Satisfaction Questionnaire (AneurysmTSQ). Results The questionnaires were sent to 297 patients with abdominal aortic aneurysm (AAA) or who had undergone AAA repair (using open or endovascular technique) sampled from five UK NHS Trusts. Exploratory Factor Analysis was used to examine factor structure together with reliability analysis. A subset of 65 patients completed the questionnaires a second time four months later. One hundred and ninety-seven patients (178 men; 18 women) provided data for analysis (69% response rate): mean age was 75 years (range 60-95). Nineteen were under pre-operative surveillance for AAA and 178 had undergone AAA repair (70 open repair; 104 endovascular repair; 4 uncertain). Exploratory Factor Analysis of the AneurysmDQoL and the AneurysmTSQ each demonstrated a one-factor structure. The AneurysmSRQ demonstrated a six-factor structure (emotional, weight loss, lower limb, cognitive, general malaise and gastrointestinal symptoms) and a one-factor composite symptom scale. All scales have clean factor structures: item loadings above 0.40, no cross-loadings, and no factors with fewer than three items. Internal consistency reliability was excellent (α = 0.869-0.959) and test-retest reliability good (Intraclass correlation coefficient = 0.70-0.88). Conclusions The three new questionnaires have a clear structure and strong reliability and are now ready for use in clinical trials and routine practice, which will allow evaluation of responsiveness to change.